Cytoprotective effect of selective small-molecule caspase inhibitors against staurosporine-induced apoptosis - Wu J; Wang Y; Liang S; Ma H (Dove Medical Press, 2014)
Jianghong Wu, Yuren Wang, Shuguang Liang, Haiching Ma Reaction Biology Corp, Malvern, PA, USA Abstract: Caspases are currently known as the central executioners of the apoptotic pathways. Inhibition of apoptosis and promotion of normal cell survival by caspase inhibitors would be a tremendous benefit for reducing the side effects of cancer therapy and for control of neurodegenerative disorders such as Parkinson's, Alzheimer's, and Huntington's diseases. The objective of this study was to discover small-molecule caspase inhibitors with which to achieve cytoprotective effect. We completed the high-throughput screening of Bionet's 37,500-compound library (Key Organics Limited, Camelford, Cornwall, UK) against caspase-1, -3, and -9 and successfully identified 43 initial hit compounds. The 43 hit compounds were further tested for cytoprotective activity against staurosporine-induced cell death in NIH3T3 cells. Nineteen compounds were found to have significant cytoprotective effects in cell viability assays. One of the compounds, RBC1023, was demonstrated to protect NIH3T3 cells from staurosporine-induced caspase-3 cleavage and activation. RBC1023 was also shown to protect against staurosporine-induced impairment of mitochondrial membrane potential. DNA microarray analysis demonstrated that staurosporine treatment induced broad global gene expression alterations, and RBC1023 co-treatment significantly restored these changes, especially of the genes that are related to cell growth and survival signaling such as Egr1, Cdc25c, cdkn3, Rhob, Nek2, and Taok1. Collectively, RBC1023 protects NIH3T3 cells against staurosporine-induced apoptosis via inhibiting caspase activity, restoring mitochondrial membrane potential, and possibly upregulating some cell survival-related gene expressions and pathways. Keywords: cell death, caspase inhibition, mitochondria, RBC1023